A CLINICAL STUDY ON GERIATRIC DISORDER - INSOMNIA WITH SHIROBASTI AND MANSYADIKWATHA - C S Tanmane, (International Journal of Applied Ayurved Research, 2016)
Insomnia is a sleeping disorder characterized by persistent difficulty in falling asleep or staying asleep despite the opportunity. It is one of the worrying problems in most of geriatric population. Aim and Objective:To evaluate and compare the relative efficacy nidrakar effects of the Mansyadikwatha and Shirobasti in Geriatric people suffering from insomnia. Material and Methods: It was randomized controlled single blind clinical study. In this study, 30 clinically diagnosed cases of geriatric-Insomnia were selected randomly. Discussion:In this clinical trial 30 patients of Insomnia were treated to see the effect of shirobasti and mansyadikwatha. During the description of Nidranasha it is evident that the vatadosha, pittadosha, Rajoguna and sandnyavahastrotas play important role in the formation of samprapti of Anidra, so the vitiation of these factors leads to the disease Anidra in old people. Conclusion: After completion of clinical trial it was observed that there was a considerable improvement in feeling of wellbeing, physical and mental fitness in all the patients of in these two groups.